The protective and detrimental effects of self-construal on perceived rejection from heritage culture members - Ferenczi, Nelli; Marshall, Tara C.; Bejanyan, Kathrine (Frontiers in Psychology, 2015)
Individuals may perceive themselves as interdependent and similar with close others, or as independent and distinct. Do these differences in self-construal influence perceptions of rejection from those closest to us? Few studies have investigated the antecedents of intragroup marginalisation – the perception of rejection from family and friends due to not conforming to the prescribed values and expectations of one’s heritage culture. Furthermore, the implications of perceived intragroup marginalisation for psychological adjustment and an integrated bicultural identity are unclear. To gauge the effects of self-construals on perceived intragroup marginalisation and psychological adjustment (i.e., subjective well-being and flourishing) and an integrated bicultural identity, we increased the cognitive accessibility of independent and interdependent self-construals through a priming manipulation. Participants were recruited via Amazon MTurk and completed the measures online. Our results showed that priming an interdependent self-construal decreased perceived intragroup marginalisation from family and, in turn, poor psychological adjustment and bicultural identity conflict. Conversely, participants primed with an independent self-construal reported increased perceptions of intragroup marginalisation from their family and, in turn, decreased psychological adjustment and increased identity conflict. These findings support the benefits of an interdependent self and the disadvantages of an independent self for minimizing perceived exclusion from heritage culture members.